2022
DOI: 10.3390/microorganisms10061183
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic Expression of Plasmodium vivax vir Genes in P. falciparum Affects Cytoadhesion via Increased Expression of Specific var Genes

Abstract: Plasmodium falciparum-infected erythrocytes (PfIEs) adhere to endothelial cell receptors (ECRs) of blood vessels mainly via PfEMP1 proteins to escape elimination via the spleen. Evidence suggests that P. vivax-infected reticulocytes (PvIRs) also bind to ECRs, presumably enabled by VIR proteins, as shown by inhibition experiments and studies with transgenic P. falciparum expressing vir genes. To test this hypothesis, our study investigated the involvement of VIR proteins in cytoadhesion using vir gene-expressin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 63 publications
0
1
0
Order By: Relevance
“…The database for adhesion characteristics in P. vivax parasites is now expanding [ 188 ]. Carvalho and associates first showed that PvIRs can cling to human lung endothelial cells (HLECs), Saimiri brain endothelial cells (SBECs), placental cryosections, CSA, and the cell-surface receptor ICAM-1 in a study by [ 161 ] According to Brazilian research [ 123 ], rosetting was observed in 64% of the isolates, CSA adherence in 15%, ICAM1 adhesion in 12%, and placental cryosections in 9%. Additionally, the findings of a study by [ 206 ] show that P. vivax -infected red blood cells (PvIRBCs) rosette irreversibly with normocytes and are significantly stiffer than nonrosetting PvIRBCs.…”
Section: Control Challengesmentioning
confidence: 99%
“…The database for adhesion characteristics in P. vivax parasites is now expanding [ 188 ]. Carvalho and associates first showed that PvIRs can cling to human lung endothelial cells (HLECs), Saimiri brain endothelial cells (SBECs), placental cryosections, CSA, and the cell-surface receptor ICAM-1 in a study by [ 161 ] According to Brazilian research [ 123 ], rosetting was observed in 64% of the isolates, CSA adherence in 15%, ICAM1 adhesion in 12%, and placental cryosections in 9%. Additionally, the findings of a study by [ 206 ] show that P. vivax -infected red blood cells (PvIRBCs) rosette irreversibly with normocytes and are significantly stiffer than nonrosetting PvIRBCs.…”
Section: Control Challengesmentioning
confidence: 99%